The Influence of Leadership Style and Organizational Culture on the Performance of Functional Employees Through Motivation Within the General Secretariat Regional Representative Council of the Republic of Indonesia - Nunung Ariyani; Imam Wibowo; Guswandi Guswandi (International Journal Labs, 2023)
Rapid changes in today's era of globalization are driving shifts in values and rules of the game. The implication of that result, every organization is required to change the view, that the phenomenon of competition is not something to be avoided but a challenge that needs to be faced. The purpose of this study is to determine and analyze the influence of leadership style and organizational culture on the motivation of functional employees in the DPD RI Setjen environment. The population in this study is 88 functional employees of the General Secretariat of the Regional Representative Council of the Republic of Indonesia. The type of nonprobability sampling used in this study is saturated sampling or often called census. Leadership style is very important to pay attention to considering that leaders are one of the factors for the emergence of motivation in employees. Leadership is the way a leader influences the behavior of subordinates, in order to be willing to work together and work productively to achieve organizational goals.